STRATEGI INOVASI PRODUK BERBASIS SUMBER DAYA LOKAL: STUDI KASUS PENGEMBANGAN ABON IKAN BANDENG DENGAN PENAMBAHAN LIMBAH UDANG DITINJAU DARI UJI ORGANOLEPTIK - Irtanto, Devina; Hari Minantyo; Fabiola Leoparjo; Catherine Eugene Martono; Bryan Budinata; Catherine Lorena Valentina Franoto; Joaquin Levi Toreh (ITB AAS Indonesia Surakarta, 2025)
As a maritime country, Indonesia is rich in fishery products, one of which is Wonorejo Village and Keputih Village. However, in both villages, there is an abundance of milkfish (chanos chanos) products which is a problem for the surrounding community due to the lack of knowledge about milkfish innovation products. The purpose of this product innovation is to utilize milkfish as a local product by adding shrimp waste while utilizing waste from the fishing industry. This study aims to evaluate excessive milkfish products that can be processed into shredded milkfish products with the addition of shrimp waste based on organoleptic tests which include aspects of color, aroma, taste, texture, and overall liking. Overall, shredded milkfish products with the addition of shrimp waste have the potential to be developed as an innovative food product that has added value and high selling value.